ISM and ISPS Code Implementation: Stakeholder Perspectives on Indonesian Maritime Education Effectiveness - Giovanni Battista Puteri; Abdul Rochman (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This phenomenological study investigates the effectiveness of International Safety Management (ISM) and International Ship and Port Facility Security (ISPS) Code curricula within Indonesian maritime vocational education, examining the experiences of twenty-one stakeholders, including industry professionals and recent graduates. Using interpretive phenomenological analysis, the research reveals tensions between theoretical regulatory mastery and practical implementation competency. Participants showed excellent theoretical knowledge acquisition (4.25/5.0 effectiveness), but significant deficiencies appeared in crisis management readiness (2.85/5.0) and adaptive leadership development (2.95/5.0). The findings highlight a "regulatory readiness paradox," where comprehensive classroom preparation doesn't adequately translate into operational confidence on vessels and within port facilities. This study offers new theoretical frameworks on professional competency transition and provides evidence-based recommendations for integrating experiential learning to bridge the persistent gap between theory and practice in contemporary maritime safety education. It addresses the critical question of how maritime professionals and recent graduates perceive the effectiveness of current ISM and ISPS Code curricula in preparing students for practical industry applications, and what experiential factors influence the transition from theoretical knowledge to operational regulatory competency.